The Relationship between Information Technology Tools and Knowledge Management Process in Organizations: Proposed Framework - Salem Obaid Salem Bin HADEEBA; Wan Fauziah Wan YUSOFF (Communications of International Proceedings, 2021)
Despite the importance of IT to the knowledge management process, many studies found that the role of IT in knowledge management process has not been so successful mainly because of the improper utilization and integration of information technology into knowledge management. Hence, this study proposes a theoretical framework for using information technology tools (cloud computing, online conferencing, and mobile technology) that can be used to enhance knowledge management process (knowledge sharing and knowledge application). The theoretical framework included organization culture as a mediator between information technology tools and knowledge management process.
Keywords: Information Technology; Knowledge Management Process; Organizational Culture